Effect of Faba Bean (Vicia Faba) in Growth Performance, Feed Utilization, Muscle Hardness and Crispness of Red Tilapia (Oreochromis Sp) - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2019)
Among phytochemicals, phenolic compounds are gaining an increasing interest for their health promoting properties. Faba bean has a large variability of the levels of total polyphenols in seeds. Red tilapia (Oreochromis spp.) is an abundant freshwater fish with a white ﬂesh meat. Customers prefer to fish fillet with more hardness and chewiness. Objective of this research focused on the effect of faba bean (Vicia faba) replacement in growth performance, feed utilization, muscle hardness and crispness of red tilapia (Oreochromis sp.) during rearing. The finding revealed that 30% faba bean in fish meal could improve the hardness and chewiness of red tilapia muscle while compromising to growth rate and feed utilization. This investigation was potentially applied not only for red tilapia but also for other aquaculture species so that the added value of fish cultivation could be enhanced.Keywords: Faba, Red tilapia, Hardness, Chewiness, Growth rate, Feed utilization.